Associations of Eye-Related Quality of Life With Vision, Visuomotor Function, and Self-Perception in Children With Strabismus and Anisometropia - Birch, Eileen E. (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To evaluate associations between eye-related quality of life (ER-QOL) assessed by the Child Pediatric Eye Questionnaire (Child PedEyeQ) and functional measures (vision, visuomotor function, self-perception) in children with strabismus, anisometropia, or both. Our hypothesis was that children with functional deficits would have lower ER-QOL, and if so, these associations would support the convergent construct validity of the Child PedEyeQ. METHODS: We evaluated 114 children (ages 5–11 years) with strabismus, anisometropia, or both. Each child completed the Child PedEyeQ to assess four Rasch-scored domains of ER-QOL: Functional Vision, Bothered by Eyes/Vision, Social, and Frustration/Worry. In addition, children completed one or more functional tests: visual acuity (n = 114), Randot Preschool Stereoacuity (n = 92), contrast balance index (suppression; n = 91), Readalyzer reading (n = 44), vergence instability (n = 50), Movement Assessment Battery for Children–2 manual dexterity (n = 57), and Pictorial Scale of Perceived Competence and Social Acceptance for Young Children (n = 44). RESULTS: Child PedEyeQ Functional Vision domain scores were correlated with self-perception of physical competence (r(s) = 0.65; 95% confidence interval [CI], 0.35–0.96) and reading speed (r(s) = 0.47; 95% CI, 0.16–0.77). Bothered by Eyes/Vision domain scores were correlated with self-perception of physical competence (r(s) = 0.52; 95% CI, 0.21–0.83). Moderate correlations were observed between Social domain scores and vergence instability (r(s) = –0.46; 95% CI, –0.76 to –0.15) and self-perception of physical competence (r(s) = 0.43; 95% CI, 0.12–0.73) and peer acceptance (r(s) = 0.49; 95% CI, 0.18–0.80). Frustration/Worry domain scores were moderately correlated with self-perception of physical competence (r(s) = 0.41; 95% CI, 0.10–0.71) and peer acceptance (r(s) = 0.47; 95% CI, 0.16–0.77). CONCLUSIONS: Strong and moderate correlations were observed between functional measures and Child PedEyeQ domain scores. These associations provide supporting evidence that the Child PedEyeQ has convergent construct validity.